Factors that increase external pressure to the fibular head region, but not medial region, during use of a knee-crutch/leg-holder system in the lithotomy position - Mizuno J; Takahashi T (Dove Medical Press, 2015)
Ju Mizuno,1 Toru Takahashi2 1Department of Anesthesiology and Pain Medicine, Juntendo Tokyo Koto Geriatric Medical Center, Faculty of Medicine, Juntendo University, Tokyo, Japan; 2Faculty of Health and Welfare Science, Okayama Prefectural University, Soja, Japan Background: Paralysis of the common peroneal nerve is one of the relatively common nerve injuries related to the lithotomy position with the use of a knee-crutch/leg-holder system. Several risk factors have been implicated in lithotomy position-related common peroneal nerve paralysis during operation.Materials and methods: In the present study, 21 young healthy volunteers participated in the investigation of the causes of the paralysis of the common peroneal nerve in the lithotomy position using a knee-crutch/leg-holder; Knee Crutch. We assessed the external pressure applied to the fibular head and medial regions using the Big-Mat pressure-distribution measurement system. Relationships between the peak contact pressure and physical characteristics, such as sex, height, weight, body mass index (BMI), and fibular head circumference, were analyzed.Results: The peak contact pressure to the fibular head region was greater for males than for females. For all subjects, significant positive correlations were observed between the peak contact pressure to the fibular head region and weight, BMI, or fibular head circumference. However, there was no significant difference between the peak contact pressure to the fibular head region and height for any subjects. Moreover, there was no sex-related difference in the peak contact pressure to the fibular medial region, and no significant differences between the peak contact pressure to the fibular medial region and height, weight, BMI, or fibular head circumference.Conclusion: External pressure to the fibular head region is greater for males than for females using a knee-crutch/leg-holder system in the lithotomy position. In addition, the external pressure to the fibular head region, but not the fibular medial region, increases with increasing weight, BMI, and fibular head circumference. Therefore, these patient-related characteristics may contribute to the risk of developing lower-extremity neuropathy, leading to injury or ischemia of the common peroneal nerve. Keywords: pressure-distribution measurement system, peak contact pressure, body mass index, fibular head circumference, common peroneal nerve paralysis